The use of mobile phones for the prevention and control of arboviral diseases: a scoping review - Carrillo-Diaz, Maria Angelica; Kroeger, Axel; Cardenas Sanchez, Rocio; Diaz Monsalve, Sonia; Runge-Ranzinger, Silvia (BMC public health, 2021)
The rapid expansion of dengue, Zika and chikungunya with large scale outbreaks are an increasing public health concern in many countries. Additionally, the recent coronavirus pandemic urged the need to get connected for fast information transfer and exchange. As response, health programmes have -among other interventions- incorporated digital tools such as mobile phones for supporting the control and prevention of infectious diseases. However, little is known about the benefits of mobile phone technology in terms of input, process and outcome dimensions. The purpose of this scoping review is to analyse the evidence of the use of mobile phones as an intervention tool regarding the performance, acceptance, usability, feasibility, cost and effectiveness in dengue, Zika and chikungunya control programmes.
Gesehen am 30.03.2021